2018
DOI: 10.29252/ijree.3.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Perception of Using Electronic Learning Tools in an ESP Program

Abstract: Given the burgeoning interest in the use of technology and electronic tools for educational purposes among students, this study set out with the purpose of investigating medical students' perception of using e-learning tools and applications in an English for Specific Purposes (ESP) program at an Iranian medical university. The study also aimed to discover the extent to which the students prefer to use paper dictionaries, offline mobile dictionaries, computerbased dictionaries and Internet-based dictionaries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
7
0
1
Order By: Relevance
“…They also stated that their testimonies regarding their proficiency related to language areas, such as spelling and vocabulary, were not at the level they had initially thought before working on the programme. This finding is in line with the findings of a study conducted by Alizadeh (2018) amongst the Iranian medical students using e-learning tools and applications in an English for Specific Purposes (ESP) programme. The results of Alizadeh's study indicated that some students perceived that using electronic tools and application for educational purposes in the programme was highly significant.…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…They also stated that their testimonies regarding their proficiency related to language areas, such as spelling and vocabulary, were not at the level they had initially thought before working on the programme. This finding is in line with the findings of a study conducted by Alizadeh (2018) amongst the Iranian medical students using e-learning tools and applications in an English for Specific Purposes (ESP) programme. The results of Alizadeh's study indicated that some students perceived that using electronic tools and application for educational purposes in the programme was highly significant.…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…There have been many researchers conducted studies about using ICT tools in ESP, for example, using Course/Learning Management Systems, Corpora, Wikis [5]; Edmodo [6]; Zoom [7]; E-dictionary [8]; Kahoot [9]. In short, based on the current previous studies, many different technologies, ranging from traditional to online platforms, are successfully used in ESP courses to enhance the teaching and learning development.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors contribute to whether an individual develops favorable or unfavorable attitudes toward the revolution, and consequently either adopts or rejects them. The adoption of ICT in the educational process implies that ICT benefits both lecturers and students [8][13] [14]. However, but also ICT harms students, and teachers may become fixated on the technological component rather than the subject matter [15], the difficulty in classroom control [16], and students get a short span of attention [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although quite a few tudies have been conducted to investigate topics related to ESP courses especially those offered in medical studies, many of them focuses on diverse topics except students' perception and expectation. Some studies discussed the effectiveness of teaching ESP courses for medical students (Jezo, 2014); some others on the design of an ESP course through needs analysis approach (Lodhi, 2018) and students' perception of using electronic learning tools in ESP program (Alizadeh, 2018).…”
Section: Introductionmentioning
confidence: 99%